Tinjauan Hukum Islam Terhadap Dampak Psikologis Perkawinan Anak - Achmad Nasrullah (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2022)
There are many incidents when a child who is still very excited at a young age is forced to carry out a marriage due to various existing factors. For example, minimal knowledge, low economy, accidents (pregnant out of wedlock), to customs that have become family guidelines that must be applied to family members. In the findings of researchers in Simo Mulyo Baru village, Surabaya, there were 3 children who experienced this with various different factors. The results show that the psychological impact that appears on the marriage of a child varies, such as uncontrollable emotions, lack of understanding and understanding as a wife, lack of knowledge about household knowledge. From SH who has minimal knowledge and customs that forced him to get married. SH, who was still very young, also experienced this because the economy of both his parents was low and the customs that had bound his family members. Then SA had to get married because something unexpected happened, namely getting pregnant out of wedlock so that she experienced a very heavy psychological impact not being in the household such as frequent fights, uncontrollable emotions and lack of understanding of what a wife should do for her family.